Truck platooning technology diffusion: System dynamics with matching platform consideration - Pooria Choobchian; Bo Zou; Lauryn Spearing (Transportation Research Interdisciplinary Perspectives)
Truck platooning pertains to virtually coupling trucks to cut aerodynamic drag. Despite its many benefits, the dynamics of the trucking industry in adopting this technology is not well understood. In this paper, we investigate the dynamics and particularly the impact of the presence of a matching platform on platooning technology diffusion. On the qualitative side, two positive feedback loops and a larger encompassing feedback loop are unveiled. On the quantitative side, tailored system dynamics models (SDMs) are developed to quantify the feedback loops and technology diffusion evolution. We demonstrate use of the SDMs by applying them to the US trucking industry. We find that having a matching platform can significantly accelerate the platooning technology adoption. The fuel and labor savings also substantially differ with a platform. The findings help inform decision- and policy-making towards more coordinated and beneficial truck platooning technology adoption and operations, thereby improving sustainability of freight transportation.